Estudio sobre la aplicación efectiva del artículo 446 del COOTAD en los procedimientos de expropiación ejecutados por el GAD Municipal de Cayambe en el periodo 2019-2023 - Ramírez Guarnizo, Dalton Rodrigo (2024)
The general objective of this research was to evaluate the application and effectiveness of article 446 of the Organic Code of Territorial Organization, Autonomy and Decentralization in the expropriation procedures carried out by the Municipal Autonomous Decentralized Government (GAD) of Cayambe during the period 2019-2023, a through the study of files and the respective analysis of the documents provided by this entity of the Cayambe cantón, this in order to determine the correct application of the procedures established in the COOTAD code, in order to determine if a complete compliance is being made. all the appropriate documentation regarding the necessary notifications to be able to establish a correct expropriation process. In the same way, the objective is to use different techniques in which they serve as a starting point to establish a correct investigation. In the same way, the research was carried out from a qualitative approach, with this to cover all the necessary quality parameters to be able to support this work adequately, this with a descriptive scope, since the correct application of the expropriation procedures was analyzed. in this cantón by the Municipal Gad of Cayambe. The methods used were analytical since the starting point was to accurately explore the correct application of article 446 of the COOTAD and in which it allowed to clearly verify the correct application that is carried out in this canton for the benefit of society\; and the normativist, which allowed analyzing the correct use and application of the expropriation procedures carried out in the Cayambe cantón, thus verifying the correct procedures, in the same way through the information obtained from the techniques and instruments it was possible to show that there is a low deficit as far as research in this branch and matter of law is concerned. It is concluded that all the information analyzed that the correct procedures established in article 446 are complied with and that the negotiations between the parties were always known to be properly managed, in which it does not affect the right of property, in the same way the investigation cannot be considered concluded in this field, there is a need to carry out new research in periods after 2019-2023.